The Impact of Physical Exercise on the Hippocampus in Physiological Condition and Ageing-Related Decline: Current Evidence from Animal and Human Studies - Lauretta, Giovanni; Ravalli, Silvia; Maugeri, Grazia; D’Agata, Velia; Rosa, Michelino D.; Musumeci, Giuseppe (Current Pharmaceutical Biotechnology, 2022)
Physical exercise (PE), notoriously, promotes a state of general well-being, throughout the entire human lifespan. Moreover, maintaining an adequate and regular PE habit results in a powerful preventive factor towards many diseases and may also help in managing existing pathological conditions. PE induces structural and functional changes in various parts of the body, determining biological and psychological benefits. Additionally, in the elderly, PE might represent a remarkable tool reducing cognitive impairments related to the normal aging processes and it has also been found to have an impact on neurodegenerative diseases such as Alzheimer’s disease. The present review aims to provide an overview of PE effects on the hippocampus, since it is one of the brain regions most susceptible to aging and, therefore, involved in diseases characterized by cognitive impairment.
Keywords: hippocampus